EDUCATIONAL NARRATIVES AS A PEDAGOGICAL PARADIGM: THE EPICS OF HOMER - Tilk, Maria (Acta Paedagogica Vilnensia, 2014)
This paper aims to analyze Homer’s epics as educational narratives, to identify how integral yet many-faceted is the “Big Story”(“Iliad” and “Odyssey”) and the background formed for the pedagogical paradigm of the Antique Age. In particular, the philosophic, religious, ethical, poetic, physical, and aesthetic aspects of the epics are discussed, and views on learning, teaching and a learner are focused on. The aim of the paper is to compare the paradigm, emerging from Homer’s epics, to our modern day understanding of teaching, learning, and a learner, underpinned in particular by S. Sterling’s (2011) view on the mechanical and ecological paradigm in education. We bring into discussion also the notion of sustainability as a moral precept and education for sustainability, which is widely discussed nowadays, as many authors point out the crisis of values in our societies and educational systems.
Keywords: Homer’s epics; educational paradigm; learning; teaching; values; education for sustainability